PENGARUH PENJUALAN, AKTIVITAS OPERASI DAN BEBAN PAJAK PENGHASILAN TERHADAP LABA BERSIH PERUSAHAAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020 - 2023 - Eikla Ekel Malo Ikhtiar Lbs; Iqbal, Johandri; Adinda, Pramesti Nurul (LP2M Politeknik Jambi, 2025)
This study aims to determine the extent of the effect of sales, operating activities and income tax expenses on net income. The population of this study is palm oil companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. Based on the Purposive Sampling method, the number of research samples was 6 companies. The analysis carried out in this study is a classical assumption test, multiple linear regression test, R2 determination coefficient test, hypothesis test. The measuring instrument used for this analysis is the SPSS program. The results of this study are based on (t-test), sales have no effect on partial net profit with a sig value of 0,001 > 0.05, while operating activiies have no effect on the profit with a sig value of 0,275 < 0,05, and income tax expense affects net profit partially with a sig value of 0.001 < 0.05. Simultaneously (test f), sales and income tax expenses affect net income with Fvalue calculated > Ftable which is 39,956 < 2,86.